Green ear yield and grain yield of maize after harvest of the first ear as baby corn - Silva,Paulo Sérgio L e (2006)
Baby corn (BC) consists of the corn ear harvested two or three days after silk emergence. BC is a profitable crop, making possible a diversification of production, aggregation of value and increased income. Removing the first female inflorescence induces corn to produce others, making possible to produce several BC ears or, alternatively, BC (by harvesting the first ear) and green ears or grain. The objective of this work was to evaluate green ear yield and grain yield, after harvesting the first ear as BC. Corn cultivar AG 1051 was submitted to the following treatments, in a random block design with ten replicates (52 plants per plot): BC harvesting; green ear harvesting (grain moisture content between 60 and 70%); mature ear harvesting; BC harvesting and harvesting of other ears as green or mature ears. Marketable green ears yield or grain yield produced without removing the first inflorescence were superior to the green ears yield or grain yield produced after removal of the first inflorescence harvested as baby corn. Harvesting only the first ear as baby corn, and then harvesting green ears or the mature ears, provided lower baby corn yields than that obtained by harvesting all ears as baby corn. Economically, the best net revenues would be obtained by exploring the crop for the production of green ears, green ears + baby corn, baby corn, baby corn + grain, and grain, in this order.